THE ROLE OF PUBLIC-PRIVATE PARTNERSHIPS: PROMOTING SUSTAINABLE ENERGY INFRASTRUCTURE IN MALAYSIA - Alyaa Adeela Md Sharif; Mohamad Amir Junih; Yasmin Syazwani Mohd Yazid; Hanafi Haron; Ashran Haji Idris; Mohd Haris Abdul Rani (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
Public-private partnerships (PPPs) have emerged as a powerful instrument in addressing issues in the construction of sustainable energy infrastructure, particularly in the transition to renewable energy. This study examines the legal, financial, and regulatory frameworks supporting PPPs to determine how they assist Malaysia in building sustainable energy infrastructure. It assesses the congruence of PPP models with Malaysia’s aims for energy transition, especially concerning significant renewable sources, namely solar and biomass. In this context, this paper tries to understand the implications of PPP initiatives towards sustainable development through case studies, particularly concerning how they reduce market risks and the tendency to monopolistic behaviour. Furthermore, it highlights the various regulatory and financial barriers that impede the effectiveness of public-private partnerships in Malaysia. The report contrasts Malaysia’s practices in specifying PPPs with foreign models. It proposes a policy enhancement in utilising PPPs in the development of sustainable energy in the country and addresses Malaysia’s source of low carbon economy, energy security, and infrastructure robustness. This study identifies and critiques critical legal, financial, and regulatory shortcomings, demonstrating how these structural weaknesses hinder renewable energy development in Malaysia.